Energetic Charged Particle Observations During Juno's Close Flyby of Ganymede. Issue 23 (12th December 2022) - Clark, G.; Kollmann, P.; Mauk, B. H.; Paranicas, C.; Haggerty, D.; Rymer, A.; Smith, H. T.; Saur, J.; Allegrini, F.; Duling, S.; Ebert, R. W.; Kurth, W. S.; et al.
Abstract: On 7 June 2021, NASA's Juno mission obtained unique measurements of Ganymede's magnetosphere during a close flyby that brought the spacecraft within ∼1, 000 km of its surface. Here Jupiter Energetic particle Detector Instrument observations are presented and analyzed. The electron pitch angle distributions reveal distinct regions of Ganymede's magnetosphere that can be characterized as inbound and outbound magnetospheric boundaries, a magnetotail/wake region, and Ganymede's open field line region. Evidence for energy dependent electron pitch angle structuring is also documented both outside and within Ganymede's magnetosphere. Electron precipitation is observed and mapped to Ganymede's surface along Juno's magnetic footpoint. Plain Language Summary: Not only is Ganymede the largest moon in our solar system, it is also the only moon known to generate its own internal magnetic field and mini‐magnetosphere. This makes Ganymede extremely fascinating to study. On 7 June 2021, NASA's Juno mission performed a historic flyby with a closest approach altitude of ∼1, 000 km above its surface. The data collected by Juno is providing us with new insights into this unique mini‐magnetosphere. This letter focuses on the energetic ion and electron environment that surrounds Ganymede and the features revealed by Juno's Jupiter Energetic particle Detector Instrument. Key Points: Energetic particle measurements reveal new insights into Ganymede's magnetosphere for the only close Juno flyby Electron pitch angle distributions reveal distinct regions of Ganymede's magnetosphere Evidence for energetic electron precipitation onto Ganymede's surface within the open field line region